Miteinander für morgen: Für Arbeitszeiten, die zum Leben passen - Smolenski, Tanja; Schaumburg, Stefan; Hofmann, Jörg (transcript, 2019)
IG Metall has put the issue of working hours on the agenda: for more self-determination for employees. In this book, actors describe the progression and outcome of the 2018 negotiations in the metallurgical and electronics industries and shed light on key elements of trade union action, such as justice, autonomy, solidarity and power. They see the negotiations as a practical prelude to a debate on the future of trade unions, co-determination, and participation in a changing society.